2014
DOI: 10.5812/ircmj.22045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma Oxidative Biomarkers and Conformational Modifications of Hemoglobin in Patients With Diabetes on Hemodialysis

Abstract: Background:Diabetes is associated with an increased generation of reactive oxygen species (ROS), which plays an important role in the development of oxidative stress and anemia.Objectives:The main purpose of this study was to investigate whether patients with diabetes undergoing hemodialysis (HD) were susceptible to oxidative stress and whether resulting damages affect the structure of hemoglobin (Hb) and plasma proteins.Patients and Methods:Twenty patients with diabetes undergoing HD, 20 patients with diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In the present study, there was significant increase in FRAP in end stage renal disease patients on dialysis when compared to controls. This was in accordance with many studies who observed altered nonenzymatic and enzymatic antioxidants in ESRD patients on PD and on HD [ 28 ]. We found a significant decrease in post-HD FRAP compared with predialysis levels.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, there was significant increase in FRAP in end stage renal disease patients on dialysis when compared to controls. This was in accordance with many studies who observed altered nonenzymatic and enzymatic antioxidants in ESRD patients on PD and on HD [ 28 ]. We found a significant decrease in post-HD FRAP compared with predialysis levels.…”
Section: Discussionsupporting
confidence: 93%
“…IDA is associated with mortality, hospitalization and health‐related quality‐of‐life measures. There is controversy about the susceptibility to evoked oxidative stress of cells in IDA; however, it is accepted that ROS production plays an important role in hemoglobin (Hb) oxidation and methemoglobin (metHb) production . Therefore the potential oxidative damage generated by the participation of Fe in redox reactions might be due to improper Fe compartmentalization and trafficking during IDA rather than its total accumulation in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the potential oxidative damage generated by the participation of Fe in redox reactions might be due to improper Fe compartmentalization and trafficking during IDA rather than its total accumulation in the body. 2,3 Nearly 100 oxidative DNA base damage have been identified. The most commonly encountered and well known mutagenicity is associated with 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that reactive oxygen species (ROS) production is altered during IDA. 2,3 Iron deficiency also affects the production of iron-containing proteins such as cytochrome, myoglobin, catalase (CAT), and peroxidase. In IDA, antioxidant defense system deteriorates, cellular immunity, and myeloperoxidase activities decrease.…”
Section: Introductionmentioning
confidence: 99%